2013
DOI: 10.1016/j.jprot.2013.06.023
|View full text |Cite|
|
Sign up to set email alerts
|

Peptides with angiotensin I converting enzyme (ACE) inhibitory activity generated from porcine skeletal muscle proteins by the action of meat-borne Lactobacillus

Abstract: The results of this study would enable the obtention of porcine functional foods by applying lactic acid bacteria generating bioactive peptides. ACE inhibitory peptides obtained by the hydrolytic action of L. curvatus CRL705 and L. sakei CRL1862 on sarcoplasmic proteins were analyzed. Among them, the peptide FISNHAY exhibited the highest activity and its sequence has not yet been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 35 publications
1
43
1
2
Order By: Relevance
“…It is worth noting that the ACE inhibitory peptides from goat milk found in this study possess C-terminal hydrophobic amino acid residues. Studies have indicated that binding of inhibitory peptides to ACE is strongly influenced by the C-terminal sequence [24], [25]. Hydrophobic amino acid residues with aromatic or branched side chains or proline residues at one or more positions in the C-terminal region are common features among potent peptide inhibitors [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the ACE inhibitory peptides from goat milk found in this study possess C-terminal hydrophobic amino acid residues. Studies have indicated that binding of inhibitory peptides to ACE is strongly influenced by the C-terminal sequence [24], [25]. Hydrophobic amino acid residues with aromatic or branched side chains or proline residues at one or more positions in the C-terminal region are common features among potent peptide inhibitors [23].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a few studies on the fi nal products of proteolysis have described various low and medium weight peptides, oligopeptides and free amino acids with in vitro antioxidant and antihypertensive effect in protein extracts from cured meats and fermented sausages (Broncano et al, 2012;Castellano et al, 2013;Escudero et al, 2012aEscudero et al, , 2013aEscudero et al, , 2013bEscudero et al, , 2014Sentandreu and Toldrá, 2007;Sun et al, 2009;Vaštag et al, 2010). The bioactive peptides identifi ed in recent years in dry-cured meat products are summarized in Table 1.…”
Section: Bioactive Peptides From Fermented Meat Productsmentioning
confidence: 99%
“…As DPP remain active during either a great part or the whole processing period of dry-cured meat products, their proteolytic action could contribute to the generation of antihypertensive peptides. Castellano et al (2013) derived ACE-inhibitory peptides from the hydrolysis of sarcoplasmic porcine proteins by the action of meat-borne Lactobacillus sakei CRL1862 and Lactobacillus curvatus CRL705. Both lactobacilli species were able to generate peptides with ACE-inhibitory activity, of which the most effective was peptide FISNHAY.…”
Section: Bioactive Peptides From Fermented Meat Productsmentioning
confidence: 99%
“…Bioactive peptides derived from food protein are increasingly becoming important as starting points for the development of functional ingredients and drugrelated compounds. Among various bioactive peptides, ACE inhibitory peptides have been studied extensively and a large number of ACE inhibitory peptides have been purified and identified from various food sources such as cereals (De Leo, Panarese, Gallerani, & Ceci, 2009;Shamloo, Eck, & Beta, 2015), egg (Majumder et al, 2015), milk (Zhou et al, 2012), casein (Holder et al, 2013;Yamada et al, 2013), porcine muscle (Castellano, Aristoy, Sentandreu, & Vignolo, 2013) and marine source such as oyster and lizard fish (Wu, Feng, Lan, Xu, & Liao, 2015;Xie, Kim, Ha, Choung, & Choi, 2014).…”
Section: Introductionmentioning
confidence: 99%